State Responsibility in Post-Judgment Reforestation Following Environmental Fines - Cakra Tona Parhusip; Triono Eddy; Adi Mansar; Ena Kazić Çakar (Sekolah Tinggi Hukum Bandung, 2025)
This paper critically examines the normative limitations and institutional challenges in enforcing ecological restoration through Indonesia’s environmental legal regime. While civil liability is increasingly employed as a formal mechanism to ensure environmental responsibility, the link between judicially imposed compensation and actual ecological recovery remains tenuous. Drawing on a normative legal approach, supported by doctrinal and comparative analysis, this study unpacks how the absence of a binding legal obligation to allocate environmental fines toward restoration efforts weakens the transformative potential of civil sanctions. It reveals a structural gap: courts may award environmental damages, yet the disbursement and utilization of these funds often fall into administrative obscurity, lacking transparency and measurable ecological outcomes. The argument advanced is that environmental accountability should not terminate with compensation; it must continue toward tangible rehabilitation anchored in public participation and legal oversight. The findings suggest the necessity of reformulating regulatory design, particularly by mandating the use of compensation funds for ecological purposes and embedding oversight mechanisms to monitor compliance. Such reform aligns with broader global calls to shift environmental enforcement from punitive to restorative justice frameworks. This contribution opens normative space for rethinking how environmental damages can be institutionally linked to actual restoration, beyond symbolic legality.